Evaluation of validity of digital photograph based dietary intake in school children - Erkilic, Tugce Orkun; Pekcan, Gulden (Mattioli 1885, 2020)
Study Objectives: Accurately assessing children's dietary intake is a challenging task. This study aimed to assess the dietary intake of school children using 24 hour records (RM) and digital photograph (DM) based dietary intake methods, to validate the use of a novel digital image-based food record and to assess the feasibility. Methods: This study was held in Mehmet Ozcan Torunoglu Elementary School in Ankara on 40 (50.0% boys) children. A questionnaire was applied, general characteristics, food consumption frequencies and physical activity levels of the children were assessed. Each week 5 children were recruited and 24-h record method (RM) was applied for 4 consecutive days with one day as a weekend day. For the same period by using a digital camera, the participants were instructed and demonstrated to take digital photos (DM) for all meals and snacks, before and after the consumption of foods. Anthropometric measurements (height, body weight, waist, and hip circumferences) of children were taken and body mass index (BMI), waist circumference/height ratios were calculated. Results: Mean (+/-SD) age of the boys and girls were 8.05 +/- 0.22 and 8.1 +/- 0.31 years, respectively. According to RM and DM, daily energy intakes of boys were 2226.9 +/- 613.13 and 1611 +/- 209.79 kcal (p<0.05) and girls were 1781.5 +/- 341.83 and 1404.7 +/- 258.04 kcal (p<0.05), respectively. Mean daily energy, protein, carbohydrate intakes and also the mean daily intakes of vitamins B1, B2, B6, folic acid, vitamin C, A, and E and minerals; calcium, magnesium, phosphorus, iron, and zinc were found higher in RM than DM (p<0.05). Conclusions: Dietary intakes of nutrients of children were found higher by RM than DM method, due to recording only food served on the plate but not considering the plate-waste. These results suggest that digital photographs are more feasible to use in dietary assessment in children and also to assist in RM. The use of technology is an important area of study in dietary assessment and may offer a means of addressing some of the challenges in dietary assessment in children as a practical, easy, and preferred method. For future research, DM should be evaluated in different age groups, such as in preschool children, adolescents, adults, elderly, and disabled people.
Keywords: Food Record Method; Digital Photography; Dietary Assessment; School Children